THE CONNECTION BETWEEN LANGUAGE AND CULTURE (Eureka Journal of Education & Learning Technologies, 2026)
To being a means for information interchange, language is a symbolic system that has the capacity to construct and mold symbolic realities through discourse, including identities, values, and perceptions. One way to think of language is as a linguistic manifestation of culture. It serves to preserve and communicate culture and cultural ties.
Keywords: Behaviour, culture, identity, language, communicative events.